Suomen Ateenan-instituutti : The Finnish Institute at Athens - Suomen Ateenan Instituutin Säätiö (2008)
[Dt.:] Die Seite listet unter anderem Publikationen, Veranstaltungen, Ausgrabungsprojekte und Kurse auf und informiert über Mitglieder des Instituts. Außerdem geboten: Eine Sammlung von nützlichen Links. - [Engl.:] This official website lists publications, activities, fieldwork projects as well as study programs and informs about staff and members of the institute. Moreover: A useful link collection.